1996
DOI: 10.1051/aas:1996298
|View full text |Cite
|
Sign up to set email alerts
|

Atomic data from the IRON Project. XIX. Radiative transition probabilities for forbidden lines in Fe II

Abstract: Abstract. -Radiative transition probabilities have been calculated for the magnetic dipole (M l) and electric quadrupole (E2) transitions connecting the 63 metastable levels in the 3d64s, 3d7 and 3d54s2 configurations in Fe II. The most important configuration interaction (Cl) and relativistic effects have been taken into account in the computations carried out with the help of two independent computer programs, SUPERSTRUCTURE (SST) and RELATIVISTIC HARTREE-FOCK (HFR). The results obtained in the present work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(140 citation statements)
references
References 20 publications
12
124
4
Order By: Relevance
“…The experimental A-values are given in Table 2, along with uncertainties and comparisons to calculations. The agreement with the values by Quinet et al (1996) is within our uncertainties. We estimate the uncertainty of the BFs to 6-12%, including the uncertainties in the intensity measurement, calibration, reddening and residual lines.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The experimental A-values are given in Table 2, along with uncertainties and comparisons to calculations. The agreement with the values by Quinet et al (1996) is within our uncertainties. We estimate the uncertainty of the BFs to 6-12%, including the uncertainties in the intensity measurement, calibration, reddening and residual lines.…”
Section: Resultssupporting
confidence: 89%
“…The relativistic Hartree-Fock (HFR) calculations by Quinet et al (1996) show the best general agreement with the experimental values presented in this and previous studies. The agreement is good with the exception of the b 2 H 11/2 level (Rostohar et al 2001) which differs by 5σ.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A V varies from ∼6 in the knots Z1 and S to ∼12 in the knot Z2. Fernandes (2000) found a value of A V = 9.38 ± 1.49 mag in a region that covers our knots HH46-1 and S. This value has however been derived employing the theoretical [Fe ii] 1.644/1.257 μm ratio given by the radiative rates of Nussbaumer & Storey (1988) that predict higher values with respect to the Quinet et al (1996) rates (Nisini et al 2005). On the other hand, Antoniucci et al (2008) found an A V ∼ 40 mag on-source, indicating a high density gradient towards the central object.…”
Section: Extinctionmentioning
confidence: 81%
“…To convert the observed ratios into A v values, we have adopted the radiative transition probabilities given by Quinet et al (1996) using the relativistic Hartree-Fock (HFR) computer programme. The extinction errors have been estimated directly from the flux error of each line.…”
Section: Extinctionmentioning
confidence: 99%